Operational Management in Crowd Control: A Case Study of Concerts at ICE BSD City - Novrianto Basidi Rihi; Myrza Rahmanita; Sri Mariati (Target : Jurnal Manajemen Bisnis, 2025)
This study analyzes the implementation of crowd management at international concert events held at the Indonesia Convention Exhibition (ICE) BSD City. Using a qualitative survey approach through observation, interviews, and documentation, the research evaluates nine key indicators of crowd manage- ment: crowd behavior, security management, risk management, venue layout, venue capacity, barricade placement, emergency procedures, holding areas, and building facilities. The findings show that crowd management at ICE BSD City is generally well implemented, supported by strong coordination be- tween concert promoters and venue management. This collaboration ensures audience safety, smooth crowd flow, and overall comfort during events. However, several potential risks, such as crowd distur- bances involving popular artists, artist cancellations, demonstrations, and bomb threats, are still likely to occur and require continuous mitigation through enhanced coordination with security authorities and adherence to international standards. The study also highlights the importance of structured planning, including risk assessments, layout management, and the availability of adequate emergency facilities. Limitations of this study include the small sample size and the focus on a single venue, which limit the generalizability of the findings. Future research is recommended to broaden the respondent pool, include comparisons with other venues, and examine the role of technology-based crowd management systems to provide a more comprehensive understanding of crowd control practices in large-scale events.